2021
DOI: 10.18231/j.ijceo.2021.068
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between ranibizumab and its first biosimilar razumab in terms of efficacy and safety in DME, RVO and wet AMD associated with CNVM

Abstract: To compare safety and efficacy of intravitreal therapy between anti vascular endothelial growth factor (Anti-VEGF) Ranibizumab and biosimilar Razumab in diabetic macular oedema (DME), wet age related macular degeneration (AMD) with choroidal neovascular membrane (CNVM) and retinal vein occlusion (RVO). Prospective comparative study involved 60 eyes of 56 adults, randomized into 2 groups from September 2016 to November 2017. Group 1 (n=30) received Ranibizumab (0.5mg in 0.05ml) and group 2(n=30) Razumab (0.5mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…A review conducted in 2012 showed that up to 7% of people with diabetes might be affected by DME and its risks are greatly similar to DR (Lee et al, 2015). Also, the prevalence of diabetic macular edema increased from 0% to 3% population who were recently diagnosed with diabetes and about 28% to 29% in those with known cases of diabetes for more than 20 years (Preethi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A review conducted in 2012 showed that up to 7% of people with diabetes might be affected by DME and its risks are greatly similar to DR (Lee et al, 2015). Also, the prevalence of diabetic macular edema increased from 0% to 3% population who were recently diagnosed with diabetes and about 28% to 29% in those with known cases of diabetes for more than 20 years (Preethi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%